Information Security and Cryptology 6th International Conference, Inscrypt 2010, Shanghai, China, October 20-24, 2010, Revised Selected Papers - Lai, Xuejia; Yung, Moti.; Lin, Dongdai; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 6th International Conference on Information Security and Cryptology, Inscrypt 2010, held in Shanghai, China, in October 2010. The 35 revised full papers presented were carefully reviewed and selected from 125 submissions. The papers are organized in topical sections on encryption schemes, stream ciphers, sequences and elliptic curves, secure computing, hash functions, key management, digital signatures, privacy and algebraic cryptanalysis, hashing and authentication, and hardware and software issues.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Computer Communication Networks; Data Encryption; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Systems and Data Security; Computers and Society